Beta cortical oscillatory activities and their relationship to postural control in a standing balance demanding test: influence of aging - Hu, Yang; Petruzzello, Steven J.; Hernandez, Manuel E. (Frontiers in Aging Neuroscience, 2023)
Background: Age-related changes in the cortical control of standing balance may provide a modifiable mechanism underlying falls in older adults. Thus, this study examined the cortical response to sensory and mechanical perturbations in older adults while standing and examined the relationship between cortical activation and postural control. Methods: A cohort of young (YA, 18-30 years) and older adults (OA, 65-85 years) performed the Sensory Organization Test, Motor Control Test, and Adaptation Test while high-density electroencephalography (EEG) and center of pressure (COP) data were recorded in this cross-sectional study. Linear mixed models examined cohort differences for cortical activities, using relative beta power, and postural control performance. Spearman correlations were used to investigate the relationship between relative beta power and COP indices. Results: Under sensory manipulation, OA demonstrated significantly higher relative power at all postural control-related cortical areas (P<0.01), while under rapid mechanical perturbations, OA demonstrated significantly higher relative power at central areas (P <0.05). As task difficulty increased, YA had increased relative power while OA demonstrated decreased relative beta power (P<0.01). During sensory manipulation with mild mechanical perturbations, specifically in eyes open conditions, higher relative power at the parietal area in YA was associated with worse postural control performance (P<0.001). Under rapid mechanical perturbations, specifically in novel conditions, higher relative power at the central area in older adults was associated with longer movement latency (P<0.05). Discussion: Cortical areas are increasingly recruited to maintain upright postural control, even though cortical resources may be limited, in older adults.